Virtuelles Kupferstichkabinett - Herzog August Bibliothek; Herzog Anton Ulrich-Museum (2007)
[Dt.:] Virtuelle Zusammenführung und Erschließung repräsentativer Teile der provenienzgeschichtlich eng miteinander verflochtenen druckgraphischen Sammlungen des Herzog Anton Ulrich-Museums Braunschweig (HAUM) und der Herzog August Bibliothek Wolfenbüttel (HAB). Von der DFG gefördertes Forschungsprojekt. Recherchierbare Bilddatenbank zur Druckgraphik des 15.-18. Jahrhunderts. Aus dem Bestand des HAUM wird der Schwerpunkt der Deutschen Schule abgebildet, die HAB zeigt wesentliche Teile ihrer Graphik-Sammlung aller Schulen, sowie in Bücher eingeklebte graphische Blätter. Ziel ist die Erschließung von zunächst 19.200 Blättern, die, mit den relevanten Metadaten sowie hochauflösenden stufenlos zoombaren Abbildungen versehen, frei zur Verfügung gestellt werden. Ca. 5000 überwiegend anonyme Blätter werden zusätzlich mangels signifikanter deskriptiver Metadaten mit ICONCLASS indexiert. - [Engl.:] The Virtuelle Kupferstichkabinett (Virtual Printroom) is a joint project being carried out by the Herzog August Bibliothek (HAB) in Wolfenbüttel and the Herzog Anton Ulrich Museum (HAUM) in Braunschweig, Germany. The aim of the project is to create a virtual combination of a representative selection of items from the print collections of both institutions. These include holdings which once belonged to the former ducal collections, but are now divided between the HAUM and the HAB. The main focus lays on works dating from before 1800. 32,000 prints will be digitalised in the first two years of the project, of which 19,200 will be described in detail. Descriptions and linked images will be entered into a database which are freely available via the internet. Formal descriptions are based on international standards. About 5,000 of the prints, mostly anonymous works, for which suitable descriptive metadata is not available are further indexed by Foto Marburg using of Iconclass.